The role and importance of empowering rural communities for rural development in Afghanistan - Fayaz Gul Mazloum Yar; Mahboobullah Musadiq (PT Publikasiku Academic Solution, 2024)
Empowerment of rural communities in Afghanistan has great potential to change the knowledge, attitudes and work practices of villagers. Empowerment is considered fundamental to achieving development, as progress without empowerment of marginalized communities is often considered impossible. The purpose of this study is to formulate a strategy for rural community empowerment in line with sustainable development in Afghanistan. This research utilizes qualitative content analysis of relevant sources, with data collection through document analysis. The research reviews existing studies and theories, and introduces the background of empowerment in the context of sustainable rural development. The results show that empowering rural communities can be done by utilizing local resources and increasing the capacity of individuals to innovate. Proposed strategies include improving access to education, skills training, as well as supporting local economic initiatives. Effective empowerment not only increases agricultural productivity, but also strengthens social ties and trust among community members. Empowerment is a multidimensional process that includes economic, social, cultural, psychological and environmental aspects. It is essential for achieving sustainable development in Afghanistan, where challenges such as poverty and social disparities are still widespread. Women's empowerment, in this context, is critical to the transformation of society as a whole. Empowerment of rural communities in Afghanistan is key to achieving sustainable development. With a focus on empowerment, Afghanistan can create a resilient rural population, which contributes to national stability and sustainable growth. Policy recommendations include developing inclusive empowerment strategies, improving access to education and resources, and actively involving communities in decision-making processes.